CORE & MORE – THE CONCEPT OF INTELLIGENT REPORTING FOR CORPORATE INFORMATION - Kamil Mazurkiewicz (Polityki Europejskie, Finanse i Marketing)
This article deals with the problem of a new way of reporting corporate information – the Core & More concept. Its aim is to evaluate the Core & More concept as it relates to the increasing transparency of corporate reporting as well as to the transparency of information provided to stakeholders. On the basis of a critical review of the subject literature, reports of sector institutions and interviews with representatives of business practices, the research hypothesis was verified positively. Corporate reports that conform to the standards of the Core & More concept are more transparent and the information given to stakeholders is structured. The Core & More concept allows to derogate from the silo approach of reporting. It structures information, makes it more readable and more logical to understand. The implementation of this concept, however, requires reporting persons to use abstract thinking. Additionally, while creating reports, one should have both IT skills and IT support because this concept involves, to a large extent, the use of IT tools.